Crop-Cattle Integrated Farming System: An Alternative of Climatic Change Mitigation - . Munandar; Fitra Gustiar; . Yakup; R. Hayati; A. I. Munawar (Faculty of Animal Science, Bogor Agricultural University, 2015)
An integrated farming system is one of the alternatives for climatic change mitigation. This paper reports the application of corn-cattle based integrated farming system in Agrotechno Park Center of Palembang, and discusses its impact on CO2 fixation and the reduction of methane emissions. The study was based on the data of the first 6 yr from 2003 until 2009. The CO2 fixed in the soil and plants was determined based on the content of organic C which was multiplied by the index of 3.67. The methane gas produced by Balinese cattle and its dung was observed and modified into feed rations. The results showed that soil organic C increased from 40.80 tons C/ha in the 1st yr to 66.40 tons C/ha in the 6th yr. In addition, there was organic C fixation equivalent to 93.95 tons of CO2e. Corn biomass increased from 6.67 tons/ha to 18.66 tons/ha, equivalent to an increase in the fixation of atmospheric CO2e as much as 19.80 tons CO2e/ha. The supplementation of 60%-80% grass fodder with concentrate lowered the concentration of methane gas in cattle breathing by 28.7%, from 617 ppm to 440 ppm, while the methane emissions from cattle manure decreased by 31%, from 1367 mL/head/d to 943 mL/head/d. Installing a bio digester that generates biogas served to accommodate methane gas emissions from cattle dung and used it for bioenergy. Composting reduced the formation of methane gas from cattle manure through a regular process of turning over that gives aeration and forms aerobic condition in the heap of cattle dung. Recycling produces a variety of organic products that store carbon for a longer period of time and slowed the conversion of organic C into CO2. This study showed that the diverse activities of an integrated crop-cattle farming could be an alternative solution to climatic change mitigation.Key words: integrated farming, mitigation, organic C, methane, recycling